Discovering the embodiment of the group fitness instructor : case study of group fitness instructors of Fysioline Fressi - Jahkola, Emilia (2017)
Group fitness instructors are often portrayed as physically toned and fit with healthy lifestyles overall. The aim of a group fitness class is to help participants exercise in a desired manner with motivational coaching. Instructing a class requires a combination of coordination, anticipation and moving in-line with the music. The instructor is often situated in front of the class, making the body as visible as possible. The body is also the instructor’s single most important tool at work, which is used to show movements and non-verbal messages. The complexity of the task creates an interesting platform to research the experience of embodiment and hopefully offer insight in to what the body represents for a group fitness instructor. The aim of this study is to find out what the body means for an instructor, how they experience their body, and to determine what the most significant factors are about embodiment and being a group fitness instructor. The study was conducted with a phenomenological-hermeneutic approach, aiming to take a closer look at a specific phenomenon. The research took part in a Finnish fitness center in the Tampere region. Altogether six female instructors took part in the study. The participants’ experience in instructing ranged from three years to almost 20 years. The data was gathered with the help of nine open-ended questions, which were then answered in written essays and sent via e-mail. The data was analyzed manually using conventional content analysis and four main themes arose from the results. All four themes had several sub-themes, which discussed the body of the group fitness instructor. The results showed that the instructors had a deep sense of body awareness since they view their body as a tool. The body was also seen as an instrument for communication, which also offers strong emotional experiences. Most of the participants felt that they worked in a body positive environment, even though all of them admitted to having felt body-related expectations when being in the role of the group fitness instructor. According to the results, embodiment is a prevailing concept when being a group fitness instructor, and the role of the instructor offers a unique platform to connect and understand the body. It is yet unclear where the expectations set for the body come from, and it is suggested that future research be conducted on this topic.